Structure of Sensory Organs: Sensory Receptors - qizi, Soatova Xolnisa Raxmat; oʻgʻli, Umbarov Javohir Halil; o‘g‘li, Safarov Nursulton Mamarajab; o‘g‘li, Toshniyozov Hasan Berdiyor; qizi, Rashidova Farangiz Musulmon (European Journal of Life Safety and Stability (2660-9630), 2023)
At present, we receive all sensations between our sense organs and draw conclusions. Mainly through our sense organs, we feel that food is sweet, bitter, salty, sour. The purpose of our study of cognitive analyzers is to study the etiology and pathogenesis of various diseases that occur in the language today. Key words: Sensory receptors (leaf-like, fungal-like, horn-like), sensory receptors, sensory bulbs.